Long-term observation reveals high-frequency engraftment of human acute myeloid leukemia in immunodeficient mice - Paczulla, Anna M. (Haematologica, 2017)
Repopulation of immunodeficient mice remains the primary method for functional assessment of human acute myeloid leukemia. Published data report engraftment in ~40–66% of cases, mostly of intermediate- or poor-risk subtypes. Here we report that extending follow-up beyond the standard analysis endpoints of 10 to 16 weeks after transplantation permitted leukemic engraftment from nearly every case of xenotransplanted acute myeloid leukemia (18/19, ~95%). Xenogeneic leukemic cells showed conserved immune pheno-types and genetic signatures when compared to corresponding pre-transplant cells and, furthermore, were able to induce leukemia in re-transplantation assays. Importantly, bone marrow biopsies taken at standardized time points failed to detect leukemic cells in 11/18 of cases that later showed robust engraftment (61%, termed “long-latency engrafters”), indicating that leukemic cells can persist over months at undetectable levels without losing disease-initiating properties. Cells from favorable-risk leukemia subtypes required longer to become detectable in NOD/SCID/IL2Rγ(null) mice (27.5±9.4 weeks) than did cells from intermediate-risk (21.9±9.4 weeks, P<0.01) or adverse-risk (17±7.6 weeks; P<0.0001) subtypes, explaining why the engraftment of the first was missed with previous protocols. Mechanistically, leukemic cells engrafting after a prolonged latency showed inferior homing to the bone marrow. Finally, we applied our model to favorable-risk acute myeloid leukemia with inv(16); here, we showed that CD34(+) (but not CD34(−)) blasts induced robust, long-latency engraftment and expressed enhanced levels of stem cell genes. In conclusion, we provide a model that allows in vivo mouse studies with a wide range of molecular subtypes of acute myeloid leukemia subtypes which were previously considered not able to engraft, thus enabling novel insights into leukemogenesis.